2014
DOI: 10.1007/s10336-013-1029-1
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal variation in day length and working day length has a confounding effect when comparing nest attentiveness in tropical and temperate species

Abstract: During incubation tropical passerines have been shown to have lower levels of nest attentiveness than their counterparts at north temperate latitudes, spending a higher percentage of daylight time off the nest. This difference has been interpreted as evidence of parental restraint; tropical birds allocate more time to daily self-maintenance, perhaps preserving their higher annual survival rates and future breeding potential. But such comparisons are susceptible to the confounding effects of day length variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
2
12
1
Order By: Relevance
“…Provisional findings have shown that Stripe-breasted Tits lay smaller clutches than north temperate Great Tits, have slower provisioning rates, sometimes breed cooperatively (Shaw 2003;Yatuha and Dranzoa 2010), and may have a higher annual survival rate (c. 0.75; P. Shaw, unpublished) than is typical of adult Great Tits (c. 0.50; Perrins 1979). Contrary to expectations, the two species show similar levels of nest attentiveness (Shaw and Cresswell 2014).…”
Section: Introductioncontrasting
confidence: 93%
“…Provisional findings have shown that Stripe-breasted Tits lay smaller clutches than north temperate Great Tits, have slower provisioning rates, sometimes breed cooperatively (Shaw 2003;Yatuha and Dranzoa 2010), and may have a higher annual survival rate (c. 0.75; P. Shaw, unpublished) than is typical of adult Great Tits (c. 0.50; Perrins 1979). Contrary to expectations, the two species show similar levels of nest attentiveness (Shaw and Cresswell 2014).…”
Section: Introductioncontrasting
confidence: 93%
“…Increasingly some research groups are focusing work in tropical areas (e.g. Martin et al 2000Martin et al , 2015Ghalambor and Martin 2001;Shaw and Cresswell 2014), but we urge scientists with access to these and other relatively unstudied areas (i.e. boreal regions or arid habitats) to initiate the collection of baseline nesting and nest predator data.…”
Section: Biases That Currently Exist In Nest Predation Researchmentioning
confidence: 99%
“…Incubation attentiveness affects egg temperature, and hence offspring traits, but inferences in comparative studies are sensitive to whether attentiveness is measured during the day or over a 24‐h period (Shaw and Cresswell ). Compared to 24‐h attentiveness, daytime attentiveness more closely reflects the ways in which parents trade‐off investment in reproductive effort versus adult self‐maintenance, particularly when incubation is done by a single sex and eggs cool while the parent forages or is otherwise off the nest (White and Kinney ).…”
Section: Introductionmentioning
confidence: 99%